2004 IEEE International Conference on Industrial Technology, 2004. IEEE ICIT '04.
DOI: 10.1109/icit.2004.1490730
|View full text |Cite
|
Sign up to set email alerts
|

A new quantum-inspired genetic algorithm for solving the travelling salesman problem

Abstract: This paper presents anew algorithm for solving the Travelling Salesmm Problem (TSP). The TSP is one of the most known combinatorial optimisation problems. It is about finding the shortest Homilronian cycle relating N cities. The algorithm is inspired from both genetic aigorithms and quantum compirting fields. It exrends the standard genedic dgorifhms by combining them to some concepts and principles provided from quantum computing field szich as giiantum bit, states superposition and intetfterence. The obfaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 2 publications
0
29
0
Order By: Relevance
“…It uses crossover and mutation operators to replace the bQIEAo migration operators. According to the bQIEAcm reported in Li et al (2005a), Xu et al (2005), Meshoul et al (2005aMeshoul et al ( , 2005b, Wang et al (2005c), Yang et al (2004aYang et al ( , 2004bYang et al ( , 2005; Talbi et al (2004aTalbi et al ( , 2004bTalbi et al ( , 2004c, Li and Zhuang (2002), Abdesslem et al (2006), Yang and Jiao (2003), Guo et al (2007), Yang and Ding (2007), Shu (2007), Wei et al (2008), Ding et al (2008), Zhao et al (2009), the pseudocode algorithm can be summarized as shown in Fig. 6.…”
Section: Bqieacmmentioning
confidence: 94%
“…It uses crossover and mutation operators to replace the bQIEAo migration operators. According to the bQIEAcm reported in Li et al (2005a), Xu et al (2005), Meshoul et al (2005aMeshoul et al ( , 2005b, Wang et al (2005c), Yang et al (2004aYang et al ( , 2004bYang et al ( , 2005; Talbi et al (2004aTalbi et al ( , 2004bTalbi et al ( , 2004c, Li and Zhuang (2002), Abdesslem et al (2006), Yang and Jiao (2003), Guo et al (2007), Yang and Ding (2007), Shu (2007), Wei et al (2008), Ding et al (2008), Zhao et al (2009), the pseudocode algorithm can be summarized as shown in Fig. 6.…”
Section: Bqieacmmentioning
confidence: 94%
“…quantum logic gates), quantum-inspired computing could help quantum hardware platforms to be feasible. The increased performance of Quantum-inspired Genetic Algorithms with respect to classical Genetic Algorithms has been recently demonstrated for some classical combinatorial optimization problems, such as the travelling salesman problem (Talbi et al, 2004).…”
Section: Quantum-inspired Genetic Algorithmsmentioning
confidence: 99%
“…The main principle of GA [3] Selection. Selection is to evaluate each individual and keeps only the fittest ones among them.…”
Section: Main Process Of Ga and Greedy Algorithmmentioning
confidence: 99%
“…These problems require very usually a colossal amount of computing resources to be solved efficiently because the solutions space that should be explored gains exponentially when the size of the problem increases [3].…”
Section: Introductionmentioning
confidence: 99%